2015
DOI: 10.1016/j.fuproc.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis and char reactivity of a poor-quality refuse-derived fuel (RDF) from municipal solid waste

Abstract: • Increasing both heating rate and peak temperature led to more reactive RDF chars. 2• The co-pyrolysis of the RDF and two-phase olive mill waste was also investigated. 3• The reactivity of resulting TPOMW chars increased in the presence of RDF. 4• The carbonization efficiency of TPOMW was improved in the presence of RDF. 5• Results motivate further studies on the use of this RDF as pyrolysis additive.The present study focuses on analyzing the pyrolysis and combustion behaviors of a refuse-8 derived fuel (RDF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…With the increase of the final microwave irradiation temperature, the pore surface area, total pore volume and mean diameter were significantly increased. In addition, the increase of surface area was in good agreement with Manya et al (2015). They reported a marked increase in pore surface area when the peak temperature was increased during pyrolysis of poor quality RDF.…”
Section: Scanning Electron Microscopy and Pore Volume And Pore Surface Of The Modified Rdfsupporting
confidence: 78%
“…With the increase of the final microwave irradiation temperature, the pore surface area, total pore volume and mean diameter were significantly increased. In addition, the increase of surface area was in good agreement with Manya et al (2015). They reported a marked increase in pore surface area when the peak temperature was increased during pyrolysis of poor quality RDF.…”
Section: Scanning Electron Microscopy and Pore Volume And Pore Surface Of The Modified Rdfsupporting
confidence: 78%
“…In a recent publication, Manyà et al 33 have reported on a noticeable increase in the fixedcarbon yield (i.e., carbonization efficiency) for the pyrolysis of OW at 600 °C and atmospheric pressure with 10 wt. % of a rejected material from MSW composting (RC) in the physical mixture.…”
Section: Introductionmentioning
confidence: 99%
“…The best combustion characteristic was obtained when the dosage of chlorine depleted pyrolyzate was 10% w/w RDF [36]. The same optimum 10 wt.% RDF-derived char addition to two-phase olive mill waste prior to slow pyrolysis was reported by Manya et al [37], that supported an apparent increase in the carbonization efficiency as well as an enhancement of the resultant char's reactivity in air [37].…”
Section: Technologies In Refuse Derived Fuel and The Organic Rankine mentioning
confidence: 56%